Policing Los Angeles: Race, Resistance, and the Rise of the LAPD - Felker-Kantor, Max (Justice, Power, and Politics Ser, 2018)
Cover -- Contents -- Introduction -- Chapter 1. Policing Raceriotland -- Chapter 2. The Year of the Cop -- Chapter 3. High Noon in the Ghetto -- Chapter 4. Kid Thugs Are Spreading Terror through the Streets -- Chapter 5. Police Crimes and Power Abuses -- Chapter 6. The Rap Sheet -- Chapter 7. Policing an Internal Border -- Chapter 8. The Enemy Within -- Chapter 9. The Chickens Have Come Home to Roost -- Epilogue -- Acknowledgments -- Notes -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Y -- Z